Tuberculous Tenosynovitis of the Wrist Mimicking a Volar Wrist Ganglion Cyst and Carpal Tunnel Syndrome - Kemal GÖKKUŞ,; Ergin SAĞTAŞ,; Ahmet Turan AYDIN1, (Archives of Rheumatology, 2013)
In this article, we present a rare case of tuberculous tenosynovitis of the wrist flexor tendons. This condition should be considered in the differential diagnosis of chronic tenosynovitis and mass lesions of the wrist and the patient should receive extensive debridement and chemotherapy.